A política de reforma agrária do Incra e os conflitos no campo em Roraima - Bezerra, Josinaldo Barboza (2019)
The present thesis, entitled "The Agrarian Reform Policy of INCRA and the Field Conflicts in Roraima", gains importance in the current political and economic scenario of expansion of agribusiness and land transfer of the Union to the state domain. Roraima has a border with the Cooperative Republic of Guayana, Bolivarian Republic of Venezuela, State of Amazonas and Pará. Roraima has a strong migratory influence, with emphasis on the State of Maranhão, which represents 16% of the total. The migrants, on reaching the "new land," vie for spaces previously appropriated by political and economic forces that historically dominate local power. Part of the migrant population came to Roraima when it was still Federal Territory, encouraged by the policies to encourage the occupation of the region of the North Frontier of the Amazon, creating, for this, rural settlements. Roraima has 67 settlements managed by INCRA, with capacity to settle 22,115 families and 14,026-seat belt. Despite the apparent availability of land, there are 1,463 families in conflict over land disputes. From this juncture, the present thesis proposes to answer the following research problem: How to explain the occurrence of land conflicts in Roraima, if the number of land available for agrarian reform is greater than the number of families in conflict? The answer to this question demands to identify the model of settlements adopted by INCRA and the connections with the conflicts in the field in Roraima, constituting, therefore, the general objective of the present thesis. Specific objectives: to describe the physical aspects and the geohistorical processes in which the State of Roraima is based; to discuss the model of rural settlements adopted by INCRA in the period from 2006 to 2016; Investigate who are the settled subjects and what conditions of the lots available for settlement; and to consider the conflicts over land in Roraima. The knowledge of the political practices adopted by INCRA in the organization of the settlements can contribute to help the social movements to understand the context in which the settlements are created and to reassess the strategies of action, justifying the importance of the present thesis. The research was based on historical materialism, with a qualitative and exploratory nature. The techniques used were: documentary research; Note; interviews with structured and semi-structured questionnaire and on-site visits. The results confirm that the land in Roraima has historically been constituted as the source of the political and economic power of the dominant groups, who seek to subject the peasants to the exploitation of capital, excluding them from access to the conditions of production. The settlement model adopted by INCRA has not been sufficient to guarantee the peasants' permanence in the land; on the contrary, it has served as a strategy for occupying the spaces with low added value. It is also a way of adding value to the area and preparing the necessary conditions for the expansion of capital by expanding the pasture areas, while pushing the peasants into conflict zones.